Effectivity Announcement Of State Administrative Court Decisions With Permanent Legal Force Through Printed Mass Media - Uya, Maura Kavita (Universitas Negeri Semarang, 2024)
In this article, the author focuses on the discussion related to the implementation of BHT court decisions by providing coercive measures in the form of administrative sanctions, spending money for coercion, and announcements through printed mass media. This is a form of coercion against state administrative officials who do not implement court decisions voluntarily. This research method is juridical-normative using a statutory approach, case approach, and conceptual approach by collecting data qualitatively in the form of secondary data sources in qualitative descriptive data analysis. The findings prove that it is necessary to reform Article 116 Paragraph (5) of the Administrative Court Law, which needs revision and additional articles. Then the change from print media to electronic media, whose reach is not only in the jurisdiction but can be throughout the world with many people. Furthermore, the deletion in Article 116 Paragraph (5) of the PTUN Law related to announcements in the printed mass media that there needs to be criminal sanctions imposed if state administrative officials do not carry out PTUN court decisions.